Meningkatkan Kemampuan Bicara Anak Usia Dini Melalui Pembelajaran Menggunakan Media Wayang Modern Karakter Animasi Lucu - Arsan Shanie; Clarita Nur Fadhilah (Journal of Early Childhood and Character Education, 2021)
One of the developments experienced by early childhood is the ability to speak and speak the language. This can be stimulated by using learning media that can generate children's interest in learning. Modern wayang is a learning medium that can improve children's speaking and language skills. The purpose of this study was to determine the improvement of early childhood speech skills using modern wayang media. This research is qualitative descriptive research. The subjects in this study were children in the Ngaliyan District of Semarang. The results of this study are that children's language skills, creativity and innovation increase after being given learning through modern puppet media. Improved children's abilities include listening, responding to comments, speaking more clearly, sorting ideas, discussing and expanding vocabulary.